Keanekaragaman Fauna Ikan di Kawasan DAS Hulu Tabalong, ~abupatenT abalong, Kalimantan Selatan - Tjakrawidjaja, Agus H. (JURNAL BIOLOGI INDONESIA, 2002)
ABSTRACTFish Fauna Diversity of upper Tabalong basin area, Tabalong District, SouthKalimantan. A survey was done to examine the freshwater fish fauna of the upper Tabalongarea, with emphasis on the PT. AYI production forest area, Tabalong District, SouthKalimantan Province. Field work done 13 - 28 June 2001. Fish were sampled at 26 sites inupper Tabalong, within the Tabalong Kiwa catchment above Panaan, on the Lou tributary ofthe Kumap River, and on the Ayu tributary of the Tabalong Kanan river. Sampling was doneusing a variety of methods including siene net, cast net, and gill net, hook and line, rotenoneand electrical shock 120 volt. A total of 93 fish species were recorded, in 34 genera and 11families. The fish fauna of upper Tabalong is typical of that in rivers systems in Kalimantan,in that is dominated by Cyprinidae family 45 species (48.4%) in 18 genera, 28 species(30.1%) in five genera of which are in the Balitoridae, five species (5.4%) in two genera ofMastacembelidae, four Species (4.3%) in two genera of Bagridae, Sisoridae, Channidae andTetraodontidae each three Species (3.2%) in one genera, two (2.1%) in two genera ofCobitidae, and the end Clariidae, Synbranchidae and Osphronemidae each one species (1.1%)in one genera. Five species of fish are new record of distrbution to Borneo, one species maybe New species (in process).Keywords: Diversity, fish, species, abundance, Tabalong, Kalimantan Selatan